INFLUENCE OF PEN HOUSING WITH LITTER ON SANITARY STATUS, PERFORMANCE AND CARCASS TRAITS OF GROWING RABBITS - MACHADO, L. C.; SANTOS, A. M.; ZEFERINO, C. P.; BITTENCOURT, M. T.; GERALDO, A.; CAMARGOS, R. S.; FARIA, C. G.; GARCIA, V. C. (Ars Veterinaria, 2019)
The objective of this study was to evaluate the health status, productive performance and carcass traits of growing rabbits housed in pen with litter and conventional cage. At 35 d, 54 crossbred rabbits (New Zealand White vs. Botucatu) were randomly housed in pen with litter (6 pens, 6 rabbits/pen, 2.3 rabbits/m²) or cage (6 cages, 3 rabbits/cage, 8.3 rabbits/m²) and kept until the age of slaughter at 77 d. To simulate farm conditions, the rabbits that were housed in pen have not been previously adapted to this system. There was greater intensity of dirt and mucus occurrence in the rabbits housed in pens in first period, but the mucus occurrence practically disappeared in the later period. For performance, the rabbits housed in cages had a higher live weight at 56 d (1714 vs. 1506 g; P<0.001), as well as BWG (46.4 vs. 36.7 g/d, P<0.001) and better FC (2.75 vs. 3.33; P<0.05) from 35 to 56 d. However, these animals did not show the best performance (P>0.05) in the posterior period (56 to 77 d). There was no effect (P>0.05) of housing system for carcass yield, dissectible fat and hind leg yield. It may be suggested that rabbits adapt to the floor over time. Therefore, it is indicated the adoption of this system for growing rabbits.